Answer:
Explanation:
First, observe that:
![(n+1)^2(2(n+1)^2-1)=(n^2+2n+1)(2n^2+4n+1)=2n^4+8n^3+11n^2+6n+1](https://img.qammunity.org/2020/formulas/mathematics/college/byw80byuj2dc1k32w3lha99karqkqak5ml.png)
We will prove by mathematical induction that, for every natural,
![1^3+3^3+5^3+......(2n-1)^3=n^2(2n^2-1)](https://img.qammunity.org/2020/formulas/mathematics/college/4zcss4top2o8p2j39arxc148qeh0lyiqr4.png)
We will prove our base case (when n=1) to be true.
Base case:
![1^3+3^3+5^3+......(2n-1)^3=1=n^2(2n^2-1)](https://img.qammunity.org/2020/formulas/mathematics/college/ondhcp3tlbeu21x64wiiu6377xlk8cvkj3.png)
Inductive hypothesis:
Given a natural n,
![1^3+3^3+5^3+......(2n-1)^3=n^2(2n^2-1)](https://img.qammunity.org/2020/formulas/mathematics/college/4zcss4top2o8p2j39arxc148qeh0lyiqr4.png)
Now, we will assume the induction hypothesis and then use this assumption, involving n, to prove the statement for n + 1.
Inductive step:
![1^3+3^3+5^3+......(2(n+1)-1)^3=1^3+3^3+5^3+......(2n+1)^3=\\=n^2(2n^2-1)+(2n+1)^3=2n^4-n^2+8n^3+12n^2+6n+1=2n^4+8n^3+11n^2+6n+1](https://img.qammunity.org/2020/formulas/mathematics/college/d13j3igz44f93gvg7tmjop8ifj4o5wc9g2.png)
Then, by the observation made at the beginning of this proof, we have that
![1^3+3^3+5^3+......(2(n+1)-1)^3=(n+1)^2(2(n+1)^2-1](https://img.qammunity.org/2020/formulas/mathematics/college/7wfhxjmwbrs7mfwvazlylbyvojoasz1zh7.png)
With this we have proved our statement to be true for n+1.
In conlusion, for every natural n
,
![1^3+3^3+5^3+......(2n-1)^3=n^2(2n^2-1)](https://img.qammunity.org/2020/formulas/mathematics/college/4zcss4top2o8p2j39arxc148qeh0lyiqr4.png)
b)
Observe that
Then,
- If
- If
- If
Therefore, for every
c)
We will prove by mathematical induction that, for every natural n>3,
Inductive hypothesis:
Given a natural n>4,
[tex](n-1)^2<2n^2.[tex]
Now, we will assume the induction hypothesis and then use this assumption, involving n, to prove the statement for n + 1.
Inductive step:
[tex]((n+1)-1)^2=((n-1)+1)^2=(n-1)^2+2(n-1)+1<2n^2+2(n-1)+1=2n^2+2n- 1<2n^2+2n+1 =2(n+1)^2.[tex]
With this we have proved our statement to be true for n+1.
In conclusion, for every natural n>3,
[tex](n-1)^2<2n^2.[tex]